A constant plunge depth control strategy for robotic FSW based on online trajectory generation. (April 2023) - Xiao, Juliang; Wang, Mingli; Liu, Haitao; Liu, Sijiang; Zhao, Huihui; Gao, Jiashuang
Highlights: A method of FSW constant plunge depth control based on online trajectory generation is proposed. The proposed method can realize the autonomous tracking with a rough reference welding path. An online S-curve error compensator is proposed to track changing targets and meet the velocity, acceleration, and jerk constraints. The core of the S-curve planning is to calculate the initial jerk of each planning step. Abstract: Robotic friction stir welding (RFSW) usually comes with a huge upsetting force, and the stiffness of the welding system distributes unevenly over the position, which leads to a large deviation of the plunge depth of the tool at the end of the robot. The conventional constant distance tracking control suffers from the problem of unsmooth compensation leading to the vibration of the robot and thus degrading the weld quality. For this problem, a constant plunge depth control based on online trajectory generation for RFSW is studied, which can generate an accurate welding trajectory according to the rough initial reference path and smoothly compensate for the plunge deviation. Initially, three laser-ranging sensors are utilized to measure the pose deviation of the tool in real-time and generate the ideal welding trajectory according to the projection vector method. Then, a deformation compensation model is established to realize the real-time prediction of the correct value. To ensure the smoothness and rapidity of the dynamic tracking process of displacement deviation, we adopt an online trajectory generator as the core of optimization control to meet the process constraints such as speed, acceleration, and jerk during the compensation process. Finally, simulation and experiment are carried out. The results show that the proposed method can effectively reduce the vibration caused by compensation during the welding process and reduce flash, which can improve the welding quality.